Ozone impairs the response of isoprene emission to foliar nitrogen and phosphorus in poplar. (December 2020) - Hoshika, Yasutomo; Brilli, Federico; Baraldi, Rita; Fares, Silvano; Carrari, Elisa; Zhang, Lu; Badea, Ovidiu; Paoletti, Elena
Abstract: Tropospheric ozone (O3 ) impairs physiological processes of plants while nitrogen (N) deposition may cause imbalances in soil N and other nutrients such as phosphorus (P) suggesting an increase of P demand for plants. However, the combined effect of O3, soil N and P on isoprene emission from leaves has never been tested. We therefore examined isoprene emission in leaves of Oxford poplar clone exposed to O3 (ambient, AA [35.0 nmol mol −1 as daily mean]; 1.5 × AA; 2.0 × AA), soil N (0 and 80 kg N ha −1 ) and soil P (0, 40 and 80 kg P ha −1 ) in July and September in a Free-Air Controlled Exposure (FACE) facility. We also investigated the response of isoprene emission to foliar N, P and abscisic acid (ABA) contents in September because the 2-C-methylerythritol-5-phosphate (MEP) pathway of isoprenoid biosynthesis produces ABA. We found that O3 increased isoprene emission in July, which was associated to increased dark respiration, suggesting an activation of metabolism against O3 stress as an initial response. However, O3 decreased isoprene emission in September which was associated to reduced net photosynthesis. In September, isoprene emission was positively correlated with leaf N content and negatively correlated with leaf P content in AA. However, no response of isoprene emission to foliar N and P was found in elevated O3, suggesting that the isoprene responses to foliar N and P depended on the O3 exposure levels. Isoprene emission rate in 1.5 × AA and 2.0 × AA increased with increasing leaf ABA content, indicating accelerated senescence of injured leaves to favor new leaf growth when high O3 and nutritional availability in the soil were combined. Even though foliar N and P usually act as a proxy for isoprene emission rate, the impact of recent abiotic factors such as O3 should be always considered for modeling isoprene emission under climate change. Graphical abstract: Image 1 Highlights: We examined the interaction of O3, N and P on isoprene emission (IE) in poplar. O3 increased IE in July, but decreased it in September. IE was increased by N supply but decreased by P supply under low O3 environment. IE, however, did not depend on foliar N and P in elevated O3 in September. IE in elevated O3 positively correlated with leaf ABA content.